DINAMIKA MODERASI BERAGAMA DI INDONESIA: ANTARA IDEALISME KONSEPTUAL DAN TANTANGAN REALITAS SOSIAL - Vemby Lamara Verti Madani; Zainuddin Syarif (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study aims to highlight the idea of religious moderation as a tool to foster tolerance within Indonesia's diversity, while also identifying obstacles and providing practical recommendations for its implementation in society. Desk research, which makes use of a variety of literary sources, including publications, scientific papers, and other pertinent materials, is the technique employed. The notion, dynamics, and implementation of religious moderation in Indonesia are described through a descriptive analysis of the data. The findings demonstrate that religious moderation is essential for preserving religious harmony in the varied Indonesian community, especially as a strategy to shield society from the effects of extremism, radicalism, and intolerance. But obstacles to its implementation persist, including a restricted comprehension of religion, the impact of extremist ideologies, and precarious social circumstances. Moderate religious education, interfaith discourse, and policies promoting diversity and inclusion as the cornerstone of a harmonious national life are the means through which this research comes to the conclusion that religious moderation can be strengthened.